Green synthesis of two-electron centre based ZnO/NiCo2S4 QDs-OVs using Punica granatum fruit peel extract for an exceptional visible light photocatalytic degradation of doxycycline and ciprofloxacin. (October 2022) - Swedha, M.; Okla, Mohammad K.; Al-amri, Saud S.; Alaraidh, Ibrahim A.; Al-ghamdi, Abdullah A.; Mohebaldin, Asmaa; Abdel-Maksoud, Mostafa A.; Aufy, Mohammed; Studenik, Christian R.; Thomas, Ajith M.; Raju, Lija L.; Khan, S. Sudheer
Abstract: Biosynthesis of nanomaterials using plant extract makes them attractive in the field of photocatalysis as they are environmental friendly. The current study focused on the biosynthesis of ZnO/NiCo2 S4 QDs (NCs) using Punica granatum fruit peel extract as the reducing agent. The nanomaterials were characterized with XRD, FTIR, Raman, SEM, TEM, UV–vis DRS, BET, PL, EIS, and ESR analysis and were used for photocatalytic degradation of doxycycline (DOX) and ciprofloxacin (CIP). The bandgap of ZnO is 3.2 eV, and the decoration of NiCo2 S4 QDs aids in narrowing the bandgap (2.8 eV), making the NCs visible light active. The fabricated NCs achieved 99 and 89% degradation of DOX and CIP respectively. The photocatalytic efficiency of ZnO/NiCo2 S4 QDs was much higher compared to individual ZnO and NiCo2 S4 QDs. The half-life period of DOX and CIP were evaluated to be 58 and 152 min respectively. The percentage of TOC removal in the photodegraded product of DOX and CIP was estimated to be 99 and 89% respectively, indicating the mineralization of the compounds. The enhanced photocatalytic efficiency of the NCs was attributed to the narrowed visible light active bandgap, synergistic charge transfer across the interface, and lower charge recombination. The intermediates formed during the photocatalytic degradation of DOX and CIP were analyzed using GC-MS/MS analysis, and the photodegradation pathway was elucidated. Also, the toxicity of the intermediates was computationally analyzed using ECOSAR software. The fabricated ZnO/NiCo2 S4 QDs have excellent stability and reusability, confirmed by XRD and XPS analysis. The reusable efficiency of the NCs for the photocatalytic degradation of DOX and CIP were 98.93, and 99.4% respectively. Thus, the biologically fabricated NCs are shown to be an excellent photocatalyst and have wide applications in environmental remediation. Graphical abstract: Image 1 Highlights: ZnO/NiCo2 S4 QDs photocatalyst was synthesized using P. granatum fruit peel extract. ZnO/NiCo2 S4 QDs showed excellent photocatalytic removal of doxycycline and ciprofloxacin. The NCs showed excellent stability and reusability. Photocatalytic mechanism of ZnO/NiCo2 S4 QDs and the degradation pathway was proposed. ZnO/NiCo2 S4 QDs can be used as a promising and potential industrial wastewater treatment tool.